Incorporating tides and internal gravity waves within global ocean general circulation models: A review. (August 2022) - Arbic, Brian K.
Highlights: We review global ocean models with simultaneous tidal and atmospheric forcing. Tidal interactions with other earth system components can be studied in such models. Global internal wave models are used to plan field and satellite missions. Global internal wave models are used in operational oceanography. Global internal wave models are used to provide boundary forcing for regional models. Abstract: Until recently, high-resolution global modeling of tides has been done separately from high-resolution global modeling of the atmospherically-forced oceanic general circulation. Here we review the emerging class of high-resolution global models that are simultaneously forced by both atmospheric fields and the astronomical tidal potential. Such models simulate barotropic (surface) tides, internal tides, near-inertial motions, the eddying general oceanic circulation, and a partially resolved internal gravity wave (IGW) continuum spectrum (Garrett-Munk spectrum) simultaneously. We review the technical aspects of such global models and their myriad applications, for example, in satellite oceanography, operational oceanography, boundary forcing of regional models, tidal-cryosphere interactions, and assessment of future coastal flooding hazards in a changing climate with altered tides.